2021
DOI: 10.1101/2021.12.21.473642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polarized α-synuclein trafficking and transcytosis across Brain Endothelial Cells via Rab7-decorated carriers

Abstract: Parkinsons disease is mainly caused by aggregation of alpha-synuclein (α-syn) in the brain. Exchange of α-syn between the brain and peripheral tissues could have important pathophysiological and therapeutic implications, but the trafficking mechanism of α-syn across the blood brain barrier (BBB) remains unclear. In this study, we therefore investigated uptake and transport mechanisms of α-syn monomers and oligomers across an in vitro BBB model system. Both α-syn monomers and oligomers were internalized by prim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Consistent with this, our data show that brain endothelial cells, with more anionic membrane to maintain the brain homeostasis, provide lower permeability [75] but also more interaction with labeled αSN compared to HUVEC cells. Recently, the mechanism and trafficking route of αSN across BBB have been demonstrated, indicating monomeric αSN internalization via clathrin-dependent endocytosis and subsequent retromer-mediated endosome, as well as its polarized trafficking [21]. Furthermore, internalization and bidirectional transportation of αSN in monomeric and oligomeric form have been shown [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with this, our data show that brain endothelial cells, with more anionic membrane to maintain the brain homeostasis, provide lower permeability [75] but also more interaction with labeled αSN compared to HUVEC cells. Recently, the mechanism and trafficking route of αSN across BBB have been demonstrated, indicating monomeric αSN internalization via clathrin-dependent endocytosis and subsequent retromer-mediated endosome, as well as its polarized trafficking [21]. Furthermore, internalization and bidirectional transportation of αSN in monomeric and oligomeric form have been shown [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the mechanism and trafficking route of αSN across BBB have been demonstrated, indicating monomeric αSN internalization via clathrin-dependent endocytosis and subsequent retromer-mediated endosome, as well as its polarized trafficking [21]. Furthermore, internalization and bidirectional transportation of αSN in monomeric and oligomeric form have been shown [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 It has also been shown that α-syn monomers colocalize with markers for late endosome/lysozyme Rab7 and the retromer protein VPS35 in brain endothelial cells after uptake from media. 41 Furthermore, mitochondrial fragmentation has been observed in a PD disease mouse model with a heterozygous (D620N) mutation of Vacuolar Protein Sorting 35 (VPS35). 42 PD with disease mutation D620N VPS35 resembles sporadic PD, indicating that common mechanisms may underlie both familial and sporadic PD.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%